Experimental studies on shear behaviour of fiber reinforced prestressed concrete hollow core slabs at ambient and under fire conditions - Goh, Begonia Wei Lyn (2019)
Precast concrete was pioneered in the early 20th century. Since then, precast concrete is commonly used in construction. The process of producing precast concrete involves casting in a mould followed by curing in a controlled environment, thereby ensuring quality of the concrete as compared to casting and curing on-site. Following is the introduction of precast, prestressed concrete hollow core (PCHC) slabs, and they are widely used due to the benefits it brings about.